2020
DOI: 10.3390/ijerph17051542
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Subjective Outcomes of Barbed Reposition Pharyngoplasty for Obstructive Sleep Apnea Syndrome Treatment

Abstract: Background: The purpose of this study was to evaluate long-term subjective outcomes of barbed reposition pharyngoplasty for obstructive sleep apnea syndrome (OSAS) treatment using a specific questionnaire, the Palate Postoperative Problem Score (PPOPS). Methods: 140 patients who underwent barbed reposition pharyngoplasty (BRP) surgery in the Morgagni Pierantoni Hospital of Forlì, Italy were enrolled in the study. Postoperative outcomes were evaluated in a short- and long-term follow-up using the PPOPS question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 27 publications
0
22
0
2
Order By: Relevance
“…Different oxidative stress pathways can influence the production of NO, such as the synthesis of peroxynitrite by interaction with superoxide or the action of dimethylarginine (ADMA). It interferes with the formation of NO at high levels, the activity of the enzyme dimethylarginine dimethylaminohydrolase is reduced, leading to higher ADMA levels [ 13 , 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Different oxidative stress pathways can influence the production of NO, such as the synthesis of peroxynitrite by interaction with superoxide or the action of dimethylarginine (ADMA). It interferes with the formation of NO at high levels, the activity of the enzyme dimethylarginine dimethylaminohydrolase is reduced, leading to higher ADMA levels [ 13 , 92 , 93 ].…”
Section: Resultsmentioning
confidence: 99%
“…As described by several authors, OSAS is associated with an increased incidence of cardiovascular diseases such as high blood pressure, ischemic heart disease, arrhythmias, and cerebrovascular problems. Its treatment with increasingly innovative methods provides promising results on reducing associated comorbidities but Continuous Positive Airway Pressure (CPAP) therapy remains a fundamental approach [ 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using a "barbed" suture, the palatopharyngeal muscle is relocated into a more lateral and anterior position in order to enlarge and stabilize the velopharyngeal region. Good outcomes in terms of AHI reduction and less frequent postoperative complications after barbed repositioning pharyngoplasty for OSA was reported in a recent study by Iannella et al 41 However, surgery should be carefully evaluated in elderly patients with OSA; anesthesiological risks, possible surgical complications, and the risk of surgical failure should be considered before choosing this treatment option. [1][2][3][4][5] In this context, in a recent observational study, Gouveia et al 10 analyzed surgical complications in 107 patients with OSAS older than 65 years of age and showed that elderly patients undergoing sleep surgery had an increased risk of postoperative complications compared with younger people treated with the same procedures.…”
Section: Weight Lossmentioning
confidence: 93%
“…Of the different lateral pharyngoplasty techniques used, barbed reposition pharyngoplasty (BRP) has recently become one of the most practiced palatal surgery techniques in different countries 97 : performed with barbed suture, i.e. knotless bidirectional resorbable suture, it allows obtaining suspension of the palatopharyngeal muscle to stable structures such as the pterygomandibular raphe, with consequent expansion of the lateral walls of the oropharynx without tissue resection of the soft palate region.…”
Section: Surgerymentioning
confidence: 99%